A zebrafish model of Ifih1-driven Aicardi–Goutières syndrome reproduces the interferon signature and the exacerbated inflammation of patients - Bernal-Bermúdez, Beatriz; Martínez-López, Alicia; Martínez-Morcillo, Francisco J.; Tyrkalska, Sylwia D.; Martínez-Menchón, Teresa; Mesa-del-Castillo, Pablo; Cayuela, María L.; Mulero, Victoriano; García-Moreno, Diana (Frontiers in Immunology, 2023)
Type I Interferonopathies are a heterogenic group of rare diseases associated with an increase of type I interferon (IFN). The main challenge for the study of Type I interferonopathies is the lack of a well-founded animal model in which beIer characterize the phenotype as well as to perform fast and large drug screenings to offer the best treatment opLons. In this study, we report the development of a transgenic zebrafish model of Type I interferonopathy overexpressing ifih1 carrying the mutaLon p.Arg742His (Tg(ifih1_mut)), corresponding to the human mutaLon p.Arg779His. RNA sequence analysis from Tg(ifih1_mut) larvae revealed a systemic inflammaLon and IFN signature upon a subopLmal poly I:C inducLon compared with wild type larvae, confirming the phenotype observed in paLents suffering from Type I interferonopathies. More interesLngly, the phenotype was manifested in the zebrafish inflammaLon and Type I IFN reporters n/b:eGFP and isg15:eGFP, respecLvely, making this zebrafish model suitable for future high throughput chemical screening (HTS). Using the unique advantages of the zebrafish model for gene ediLng we have generated Tg(ifih1_mut) knocked down for mavs and ikbke, that completely abrogated the Poly I:C inducLon and acLvaLon of the GFP of the reporters. Finally, we used an FDA approved drug, BariciLnib (Jak1/Jak2 inhibitor), which was able to reduce the inflammaLon and the ISGs expression. Our results demonstrate the potenLal of this model to further understand AGS pathological mechanisms and to idenLfy novel therapeuLc drugs by HTS.